2020
DOI: 10.1071/an19183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grazing different forage systems prior to and during mating on the liveweight, condition score, conception and reproductive rate of maternal-composite ewe lambs

Abstract: Context Economic modelling identified that mating of ewe lambs for lambing at 1 year of age has the potential to increase the profitability of sheep-production systems in south-western Victoria. In order to optimise reproductive rates, ewe lambs should weigh at least 35–40 kg, have a condition score (CS) of 3.0 at mating, and be gaining weight (100–150 g/day) during mating. However, typical perennial ryegrass (Lolium perenne L.) pastures in south-west Victoria do not support the attainment of these targets wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A more recent application of dual-purpose crops is for spring sowing of crops for grazing in late summer/autumn and harvesting in late spring/early summer in the year after sowing, which has been demonstrated to provide valuable out-ofseason grazing without impacting yield (Paridaen and Kirkegaard 2015). Research in south-west Victoria reported in this special issue (Raeside et al 2021a(Raeside et al , 2021c demonstrates that in environments where it is suitable, for example milder summer temperatures and more consistent summer rainfall, spring sowing of canola can improve diet quality in late summer/autumn, and reduce supplementary feeding costs.…”
Section: Feed Supply and Livestock Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent application of dual-purpose crops is for spring sowing of crops for grazing in late summer/autumn and harvesting in late spring/early summer in the year after sowing, which has been demonstrated to provide valuable out-ofseason grazing without impacting yield (Paridaen and Kirkegaard 2015). Research in south-west Victoria reported in this special issue (Raeside et al 2021a(Raeside et al , 2021c demonstrates that in environments where it is suitable, for example milder summer temperatures and more consistent summer rainfall, spring sowing of canola can improve diet quality in late summer/autumn, and reduce supplementary feeding costs.…”
Section: Feed Supply and Livestock Productionmentioning
confidence: 99%
“…Canola was a common dualpurpose crop used across sites. Research at Hamilton demonstrated that reproductive rates of ewe lambs that grazed canola were equivalent to or better than other feed options provided (Raeside et al 2021c). At Canberra and Wagga Wagga, ewes grazed canola during late-pregnancy and lambing.…”
Section: Feed Supply and Livestock Productionmentioning
confidence: 99%